Entrepreneurial Orientation, Psychological Capital, Entrepreneurial Strategy, and Firm Performance on Private Daycare in Indonesia: A Conceptual Paper - Baskoro, Bimmo Dwi; Radzi, Rafisah Mat; Omar, Norziani Dahalan (European Scientific Journal, ESJ, 2022)
This paper aims to develop a conceptual model of the nexus of entrepreneurial orientation, psychological capital, entrepreneurial strategy, and firm performance in private daycare in Indonesia. This paper develops a conceptual model to look at the performance of daycare businesses in Indonesia based on a literature review by integrating relevant theories (such as entrepreneurial orientation, entrepreneurial strategies, and psychological capital) and logical reasoning. Research hypotheses are given to stimulate follow-up research. Based on the conceptual model, improving the performance of daycare business can be accomplished by the influence of the dimensions of entrepreneurial orientation, the role of business strategy mediation, and the moderation of psychological capital. It is hoped that empirical studies will be conducted to validate the relationship and interrelationships between related concepts and constructs in providing practical implications in the daycare business.